(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article recommends using the experience of advanced foreign countries in managing food industry enterprises. In addition, this article shows how to monitor the quality of performance of assigned tasks by employees at the enterprise and the perfect implementation of management instructions.